The diagnostic value of blood metagenomic next-generation sequencing in patients with acute hematogenous osteomyelitis - Zhang, Bingshi; Chen, Xiao; Yao, Xiaowei; Li, Mengnan; Li, Zhijie; Liu, Bo; Liu, Sikai; Liu, Zeming; Huo, Jia; Han, Yongtai (Frontiers in Cellular and Infection Microbiology, 2023)
Aims This study aims to evaluate the diagnostic value of blood metagenomic next-generation sequencing (mNGS) in detecting pathogens from patients clinically diagnosed as acute hematogenous osteomyelitis (AHO). Methods This retrospective study enrolled 66 patients with AHO. The test results of mNGS and bacterial culture on different samples, including blood and puncture fluid samples, from patients with AHO were compared to explore the diagnostic value of blood mNGS. Besides, this study also explored the efficacy of blood mNGS in decision making for antibiotic administration and analyzed the factors associated with the positive result of blood mNGS. Results The most common causative pathogens were Staphylococcus and Streptococcus. The sensitivity of blood mNGS (77.3%) was higher than that of blood culture (42.4%) (P<0.001), while the turnaround time of blood mNGS (2.1±0.4 d) is much less than that of blood culture (6.0±2.1 d) (P＜0.001). Besides, the sensitivity of blood mNGS tests (77.3%) was slightly lower than that of puncture fluid mNGS (89.4%). Furthermore, detection comparison at pathogen level unravels that blood mNGS might be suitable for diagnosing AHO caused by common pathogens, while puncture fluid mNGS could be considered as preferred examination in diagnosing AHO caused by uncommon pathogens. Finally, three independent factors associated with the true positive result of blood mNGS in patients with AHO were identified, including Gram-positive pathogens (OR=24.4, 95% CI = 1.4-421.0 for Staphylococcus; OR=14.9, 95%CI= 1.6-136.1 for other Gram-positive bacteria), body temperature at sampling time (OR=8.2, 95% CI = 0.6-107.3 for body temperature of >38.5℃; OR=17.2, 95% CI = 2.0-149.1 for patients who were chilling), and no use of antibiotics before sampling (OR=8.9, 95% CI =1.4-59.0). Conclusion This is the first report on evaluating and emphasizing the importance of blood mNGS in diagnosing AHO. Blood sample might be an alternative sample for puncture fluid for mNGS, and its extensive application in diagnosing AHO could be expected.